The Impact of Covid-19 on Nigerian Education System - Anyika, Vincent Okwudiba; Anikelechi, Ijeoma Genevieve; Thobejane, T. D. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
At a time when the Nigerian schools are on a temporary closure following the outbreak of the COVID-19 pandemic, this paper looked inwards and reflected on the nature of the education system and revealed its myriads of problems. The COVID-19 pandemic indeed had a huge impact on the educational system in Nigeria. It brought about the cessation of all learning activities in Nigeria except for private universities and secondary schools that swiftly switched to virtual learning platforms. It also illuminated the digital divide between the Nigerian student and his counterparts in other climes. COVID-19 pandemic outbreak also offered an opportunity for the nation to realise the poor status of its educational system. Some of the major problems that have confronted the Nigerian education system, as revealed by this paper, include poor funding, inadequate and dilapidating infrastructure, inadequate teaching facilities, poor teachers’ welfare, poor research funding, poor quality of teachers, unconducive learning environment, and the like. The study recommends for the exhibition of sufficient political will by the political leadership for the transformation of the education system as well as the sustained commitment of other stakeholders such policymakers and educational administrators for the transformation of the system to give it its rightful place in our national life.